DETERMINANTS OF WORK MOTIVATION AMONG DOCTORS AT COMMUNITY HEALTH CENTERS IN INDONESIA - Rusdiana Rusdiana; Achmad Fickry Faisya; Haerawati Idris (Jurnal Administrasi Kesehatan Indonesia)
Introduction: Effective work motivation among healthcare professionals significantly enhances health service performance and plays a pivotal role in improving service quality.